Laminin Receptors in the CNS and Vasculature - Yao, Yao (Stroke (1970), 2025)
Laminin exerts a variety of important functions via binding to its receptors, including integrins and dystroglycan. With the advance in gene-targeting technology, many integrin/dystroglycan knockout/mutant mice were generated in the past 3 decades. These mutants enable loss-of-function studies and have substantially enriched our knowledge of integrin/dystroglycan functions. In this review, we summarize the functions of laminin receptors during embryonic development and in the central nervous system and vasculature. First, the biochemical properties of integrins and dystroglycan are briefly introduced. Next, we discuss loss-of-function studies on laminin receptors, including integrin-α3, integrin-α6, integrin-α7, integrin-β1, integrin-β4, and dystroglycan, focusing on embryonic development, the central nervous system, and vasculature. The phenotypes of compound knockout mice are described and compared with that of single mutants. Last, important questions and challenges in the field as well as potential future directions are discussed. Our goal is to provide a synthetic review on loss-of-function studies of laminin receptors in the central nervous system and vasculature, which could serve as a reference for future research, encourage the formation of new hypotheses, and stimulate new research in this field.